Thermodynamics of Solutions of Hydrocarbons in Low Molecular Weight Poly(isobutylene) : A Gas Chromatographic Study - Castells, Reynaldo César (1996)
The reduced chemical potentials (χ*) of 20 normal and branched alkanes, cyclohexane, and three aromatic hydrocarbons at infinite dilution in poly(isobutylene) (PIB) were measured by gas liquid chromatography at five temperatures between 35 and 65 °C. Reduced partial molar residual enthalpies (κ*) were calculated from the temperature dependence of χ*; they are positive for PIB + alkane systems but smaller than those obtained in former chromatographic studies. Although uncertainties on κ* are at least 1 order of magnitude larger than those on χ*, binary X12 Flory parameters obtained from κ* display a good correlation with the structural parameter θe1, defined as the ratio of the number of hydrogen atoms on methyl groups to the total number of hydrogen atoms in the alkane molecule. Very poor or nil correlation exists between X12 values obtained from χ* and θe1. The evidence is by no means conclusive, but in principle the χ* results obtained for PIB + alkane systems could be explained in terms of free volume contributions and the antipathy between methyl groups on the alkane molecules and the polymer side groups. Positive partial molar residual entropies were detected for the three aromatic hydrocarbons; their partial molar residual enthalpies are however highly positive, resulting in their poor solvent properties toward PIB.